A Gender-Based Comparative Analysis of Learning Adjustment in Elective Subjects: A Cross-Sectional Study in Indonesia - Rina Nurlaili; Nurfarhanah; Zadrian Ardi; Dina Sukma (Jurnal Pendidikan Terapan, 2026)
Purpose: Learning adjustment among students is a crucial aspect in fostering strong academic achievement, particularly in elective courses. With effective learning adjustment, students become better able to set clear academic goals, focus on learning activities, and successfully meet all academic demands. Various factors influence students’ learning adjustment, one of which is gender. This study aims to conduct a comparative analysis of learning adjustment in elective subjects between male and female students. Methods: This study employed a quantitative approach using a comparative method. Sampling was conducted using total sampling, with a sample size of 194 Phase F students at SMA N 2 Pulau Punjung, comprising 117 female students (59.3%) and 77 male students (39.7%). The instrument used in this study was a student learning adjustment scale that had been developed and validated through expert judgment. Additionally, the instrument had undergone validity and reliability testing. The validity test results showed that all item-total correlation coefficients exceeded the r-table values. The reliability test yielded a Cronbach’s alpha score of 0.970. Data analysis was performed using the independent samples t-test. Findings: The results of the study indicate that, descriptively and overall, students’ learning adjustment at SMAN 2 Pulau Punjung falls into the high category. Next, based on hypothesis testing, it was found that women had higher scores than men, t (192) = −2.344, p = 0.020, mean difference = 7.01, 95% CI [1.11, 12.90], with an effect size based on the article’s statistical calculations of approximately Cohen’s d = 0.34, or small to moderate. Research Implications: This study provides empirical evidence that gender still influences students’ academic adjustment in specific subject area. Originality: This study offers an analysis of self-adjustment in learning, particularly in specialized subjects, which, in this context, are still very limited and have not yet been addressed.